2011
DOI: 10.1590/s0102-311x2011000100020
|View full text |Cite
|
Sign up to set email alerts
|

Perspectivas culturais sobre transmissão e tratamento da tuberculose entre os Xavánte de Mato Grosso, Brasil

Abstract: Esta nota tem por objetivo apresentar os resultados preliminares de uma pesquisa em andamento sobre as perspectivas Xavánte acerca da tuberculose (TB) e suas implicações para o tratamento e controle da endemia. Entrevistas na Terra Indígena Pimentel Barbosa, Mato Grosso, Brasil, revelaram a existência de múltiplos modelos explicativos para a doença. Os Xavánte destacam a feitiçaria (simi'õ ou abzé) e os micróbios como as principais causas de TB. Dessa forma, fazem uso de fitoterápicos assim como seguem a quimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
0
4
0
2
Order By: Relevance
“…Similarly, Welch and Coimbra Jr 22 observed that although the Xavante Indigenous from Pimentel Barbosa, MT, Midwestern Brazil, consider witchcraft to be the main cause of TB, some informants stated that the disease might also be caused by microorganisms. They found that the Xavantes believe in two types of TB, characterized by the speed of its progression: the faster type is caused by spells, and the slower one by microbes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Welch and Coimbra Jr 22 observed that although the Xavante Indigenous from Pimentel Barbosa, MT, Midwestern Brazil, consider witchcraft to be the main cause of TB, some informants stated that the disease might also be caused by microorganisms. They found that the Xavantes believe in two types of TB, characterized by the speed of its progression: the faster type is caused by spells, and the slower one by microbes.…”
Section: Discussionmentioning
confidence: 99%
“…This is because many in IT also do not provide primary health care services (5,10) , so that the geographical access is a barrier for assistance. International studies find that living in remote areas in particular can affect the health of patients by increasing the level of risk due to isolation and lack of access to health services (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Because of the socio-economic difficulties, the Indians depend exclusively on features offered by SUS (10) . This situation is worse in some regions of Brazil because even though the indigenous live in precarious economic conditions and there is limited transport in the villages, there is still a shortage of primary care services in IT to meet the population (5) , conditions also observed in international studies (6,12) .…”
Section: The Nursing Strategy To Minimize the Geographical Barrier Bementioning
confidence: 99%
“…Baniwa cosmology operates like a reception system for biomedicine information, which is appropriated and resignified according to the logic of mythical thought” (p. 281). Other studies undertaken among different ethnic groups in Amazonia show that in general Indigenous peoples are receptive to medicines provided by biomedical professionals, although they may come to be reinterpreted according to the Indigenous peoples’ own concepts regarding curative substances [ 30 , 31 , 32 ].…”
Section: Case Studies Of Nursing In Practice Among Indigenous Peoples In Brazilmentioning
confidence: 99%